2020
DOI: 10.1097/fjc.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA OIP5-AS1 Contributes to the Progression of Atherosclerosis by Targeting miR-26a-5p Through the AKT/NF-κB Pathway

Abstract: Atherosclerosis (AS) is a cardiovascular disease caused by multiple factors, leading to high mortality and morbidity in aged people. Some long noncoding RNAs have been reported to be associated with AS progression. However, the roles of OIP5-AS1 in AS development are still little known. In this study, the levels of OIP5-AS1 and miR-26a-5p in oxidized low-density lipoprotein (ox-LDL)-treated human umbilical vein endothelial cells (HUVECs) were determined by quantitative real-time polymerase chain reaction. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In arheumatoid arthritis, OIP5-AS1 was proposed to inhibit in ammation response via blocking TLR3-NF-κB pathway . In atherosclerosis, OIP5-AS1 was con rmed to facilitate cell apoptosis and in ammation by activating AKT/NF-κB pathway (Ren et al, 2020). In current study, we identi ed that miR-26a-5p negatively regulated the expression of OIP5-AS1.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In arheumatoid arthritis, OIP5-AS1 was proposed to inhibit in ammation response via blocking TLR3-NF-κB pathway . In atherosclerosis, OIP5-AS1 was con rmed to facilitate cell apoptosis and in ammation by activating AKT/NF-κB pathway (Ren et al, 2020). In current study, we identi ed that miR-26a-5p negatively regulated the expression of OIP5-AS1.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, lncRNA OPA-interacting protein 5 antisense transcript 1 (OIP5-AS1) has been reported to involve in diverse pathogeneses including tumors (Chen et al, 2019;Ma et al, 2020), myocardial ischaemia/reperfusion (MI/R) injury (Niu et al, 2020), and osteoarthritis (Zhi et al, 2020). Moreover, OIP5-AS1 was proven to regulate cell injury and in ammatory response in atherosclerosis and rheumatoid arthritis Ren et al, 2020). However, the role of OIP5-AS1 remained to be studied in ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that OIP5-AS1 is related to the pathophysiological process of atherosclerosis. A previous study demonstrated that OIP5-AS1 contributed to the progression of atherosclerosis by targeting miR-26a-5p, and OIP5-AS1 knockdown could promote cell proliferation and reduce apoptosis and inflammatory response ( 12 ). A recent integrated analysis identified six key lncRNAs, including OIP5-AS1, whose expression pattern was highly correlated with the disease stage of atherogenesis ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through searching on NCBI website, we discovered that lncRNA OIP5-AS1 is a promotive molecule in different diseases. During the process of atherosclerosis, lncRNA OIP5-AS1 targets miR-26a-5p to modulate AKT/NF-κB pathway and exerts promotion effect [20]. LncRNA OIP5-AS1 indicates dismal prognosis and mediates cell proliferation in bladder cancer through OIP5 [21].…”
Section: Discussionmentioning
confidence: 99%